Ex Libris M. Vacilevskogo [translated from Cyrillic] - Beketow, Lew (1959)
Bookplate: Three surgeons operate in front of a large open book bearing the text "Segvi il tuo corso, e lascia dir le genti." A serpent twines around a goblet to form a caduceus.